Strategy to improve adolescent knowledge on sex education: scoping review - Yustika Rahmawati Pratami; Nurul Kurniati; Nurul Mahmudah (International Journal of Health Science and Technology, 2021)
Background : Comprehensive Sexuality Education (CSE) plays an important role in preparing adolescents for safe, productive lives, and understanding about HIV and AIDS, sexually transmitted infections (STIs), unwanted pregnancy, Gender-Based Violence (GBV), and Gender inequality still pose serious risks to their well-being. Study Aim : Determine the method most instrumental in improving adolescents' knowledge about adolescent sex education and teens identify constraints in obtaining information on sex education. Methods : Stage approach to review the literature using framework Arskey and O'Malley. The framework used to manage with PEOS research questions so that the search strategy uses 5 databases, viz. Pubmed, Science Direct, Wiley, Proquest, And Ebsco with the identification of the relevant study according to the inclusion and exclusion criteria. Results: Each method has its contribution in providing information and knowledge about sex education to adolescents, however the source of the greatest role in providing sex education information mostly came from digital sources both internet and TV media. The lack of role of parents and teachers to provide enough information about sex education is reflected in the results and the above discussion. Problems in adolescent sexual behavior that negatively due to inaccurate sources such as peer and the internet and added with minimal information from parents and teachers in which teenagers hoping to get information about sex education from parents and teachers.